Barriers and challenges to smart buildings' concepts and technologies in Brazilian social housing projects. (2017) - Junior, José Alcides Gobbo; Souza, Maria Goretti Zago Nunes De; Gobbo, Simone Cristina De Oliveira
Smart building research is commonly explored in commercial buildings and less studied in the context of social housing. In this context, this article aims to diagnose the main barriers to the adoption of smart buildings' concepts and technologies in social housing projects in Brazil. The 'Expert Interviews' method was used with seven Brazilian experts in the fields of smart buildings and social housing, based on the assumption that experts have special knowledge, which are related to a special field. The main barriers categories identified in this study can be summarised in: 1) economic; 2) policy; 3) social; 4) technical. Based on these results, the study aims to contribute with possible solutions and guidelines to overcome such barriers, and discusses propositions that can be improved into hypothesis for later empirical testing.